Theoretical Compton profile of diamond, boron nitride and carbon nitride - Aguiar, Julio C. (2017)
In the present study, we used the generalized gradient approximation method to determine the electron wave functions and theoretical Compton profiles of the following super-hard materials: diamond, boron nitride (h-BN), and carbon nitride in its two known phases: βC3N4 and gC3N4. In the case of diamond and h-BN, we compared our theoretical results with available experimental data. In addition, we used the Compton profile results to determine cohesive energies and found acceptable agreement with previous experiments.